EFEKTIVITAS PEMBELAJARAN GOOGLE CLASSROOM DITINJAU DARI HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH IAIN BONE - Syahrianti, Heri; Suhra, Sarifa (JURNAL AL-QAYYIMAH, 2021)
This paper aims to describe the effectiveness of Google Classroom learning in terms of student learning outcomes of the Islamic Religious Education Study Program Faculty of Tarbiyah IAIN Bone. This type of research is descriptive qualitative research or qualitative research. The research approach is a pedagogical, information technology, and psychological approach. The subjects of this study were lecturers of Islamic Religious Education IAIN Bone which consisted of 6 people, and students of the Islamic Religious Education Study Program of the Tarbiyah Faculty of IAIN Bone, which amounted to 16 people. Data collection methods in this study used: 1) Observation, 2) Interview, 3) Documentation. Data collection and data analysis techniques used, namely 1) data reduction, 2) data presentation, and, 3) verification.The results showed that the effectiveness of the implementation of google classroom learning in the Islamic Religious Education study program on student learning outcomes, that is, it has been effective to be applied in learning, because this is stated by the active participation of students, according to the results of the recapitulation of the attendance of PAI 1 semester 2 the average percentage attendance of 96.5 and PAI 6 semester 4 with a percentage of 92.3 as well as PAI 5 semester 6 with an attendance percentage of 96.1. This is also seen in the assessment of student assignments which shows the percentage of each class, the first is PAI 1 semester 2 with a percentage of 73.3 assignments. PAI 6 semester 4 assignment percentage is 86.6 as well as PAI 5 semester 6 with assignment percentage 86.6. The effectiveness of Google Classroom can be seen through learning outcomes that can be assessed from absent attendance and student assignment collection.